OPTIMASI PORTOFOLIO PADA SAHAM PEFINDO 25 DENGAN MENGGUNAKAN MODEL MARKOWITZ (STUDI KASUS DI BURSA EFEK INDONESIA) - Made Pratiwi Dewi (Fakultas Ekonomi Universitas Warmadewa, 2021)
Fund investment activities in the capital market required expertise to minimize the investment risk. One way was to form a portfolio. Markowitz model helped investors determined the stocks which was the member of the optimal portfolio. Minimization of risk and maximization of return became the urgent thing, and the value of the return expectation became the basis of calculation. This research used non probability sampling to select Pefindo 25 indeks stocks at BEI as a population and sample. Results showed from 25 sample that only 6 (six) stocks were included in the optimal portfolio, which was Adi Sara Armada Tbk (ASSA), Wilmar Cahaya Indonesia Tbk (CEKA), Elnusa Tbk (ELSA), Erajaya Swasembada Tbk (ERAA), Champion Pacific Indonesia Tbk (IGAR), dan Vale Indonesia Tbk (INCO). The optimal investment portfolio provided total expected return portfolio was 15.592 percent and a risk of deviation / variance portfolio was 0.108 percent.